1997
DOI: 10.1021/om960961f
|View full text |Cite
|
Sign up to set email alerts
|

Planar Chiral Cp*Ru Complexes. 2.1Bis(allyl) and -(arene) Complexes Derived from (R)-Carvone

Abstract: Reaction of [Cp*RuOMe]2 (1) with either enantiomer of the naturally occurring ketonic diterpene carvone or the trimethylsilyl enolate derived thereof leads to homochiral Cp*Ru−π-complexes 6−9, where the Cp*Ru moiety is bound to either the exocyclic double bond or an allyl function derived from it as well as to an enone or ene system in the ring. Full aromatization of the cyclic enone under the same reaction conditions was achieved with 7,8-dihydrocarvone or its trimethylsilyl enolate, respectively, giving comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A distinct examplesthe diastereoselective π-complexation of a natural product, carvoneshas been studied by Koelle. 75 In particular, it was found that treatment of (R)-(-)-7,8-dihydrocarvone or its derived trimethylsilyl enol ether with [Cp*RuOMe] 2 caused a dehydrogenation resulting in the formation of the corresponding η 5 -oxocyclohexadienyl species 52 (Scheme 20). Although the substrate's central chirality was ultimately destroyed during this transformation, the preferred approach of the Cp*Ru fragment would still be expected to be anti to the isopropyl group of the terpene.…”
Section: η 5 -Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…A distinct examplesthe diastereoselective π-complexation of a natural product, carvoneshas been studied by Koelle. 75 In particular, it was found that treatment of (R)-(-)-7,8-dihydrocarvone or its derived trimethylsilyl enol ether with [Cp*RuOMe] 2 caused a dehydrogenation resulting in the formation of the corresponding η 5 -oxocyclohexadienyl species 52 (Scheme 20). Although the substrate's central chirality was ultimately destroyed during this transformation, the preferred approach of the Cp*Ru fragment would still be expected to be anti to the isopropyl group of the terpene.…”
Section: η 5 -Complexesmentioning
confidence: 99%
“…Most are derived from steroid precursors and as such have been categorized separately in this review article (see below). A distinct examplethe diastereoselective π-complexation of a natural product, carvonehas been studied by Koelle . In particular, it was found that treatment of ( R )-(−)-7,8-dihydrocarvone or its derived trimethylsilyl enol ether with [Cp*RuOMe] 2 caused a dehydrogenation resulting in the formation of the corresponding η 5 -oxocyclohexadienyl species 52 (Scheme ).…”
Section: 8 η5-complexesmentioning
confidence: 99%
“…This feature leads to a useful procedure for asymmetric reaction together with one face block by the ruthenium fragment. However, although the synthesis of planar chiral Ru complexes with an unsymmetrically substituted cyclopentadienyl ligand has been studied, only few efforts have been reported for the preparation of enantiomerically pure (η 6 -arene)ruthenium complexes with different substituents on the arene ring . , To the best of our knowledge, only one example of the synthesis of an enantiomerically pure (η 6 -arene)ruthenium Cp complex is achieved by transformation of central chirality to planar chirality of the resulting π-arene ruthenium complex. Thus, a planar chiral ruthenium complex can be prepared by aromatization of the Cp*Ru complex obtained from dihydrocarvone and [Cp*RuOMe] 2 by dehydrogenative complexation .…”
Section: Introductionmentioning
confidence: 99%
“…The resolution of enantiomeric complexes that differ through coordination of opposite Cp faces has generally relied on the generation of diastereomers via classical derivatization procedures. A chiral auxiliary must be installed onto either the Cp ligand or the metal. , The resulting diastereomers can then be separated via fractional crystallization ,,, or chromatography. , The direct generation of enantiopure complexes has been achieved by face-selective π complexation (with the help of a chiral auxiliary ligand) and through an enzyme-mediated asymmetric reaction …”
Section: Resultsmentioning
confidence: 99%